Why have labour markets reacted to the global crisis in different ways? - Eugeniusz Kwiatkowski (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper aims to identify the effects of the global crisis on employment and unemployment in the EU countries and indicate factors which may explain the differentiated response of labour markets to this crisis. Analyses show that the global economic crisis affected the labour markets of EU countries, causing declines in employment and increases in unemployment. The greatest declines in employment were observed in Greece, Estonia, Ireland, Spain, Iceland, and Portugal, and the lowest in Austria, Belgium, the Netherlands, and Poland. The greatest increase in unemployment occurred in the Baltic countries, Greece, Spain, and Portugal. The analyses indicate that the scale of changes in employment and unemployment during the global crisis depends on such factors as: the depth of the demand shock and scale of GDP adjustments; the degree of openness of the economy; the scope of alternative labour market adjustments and some labour market institutions, especially employment protection legislation and the share of fixed-term employment contracts. The analyses indicate that the smallest declines in employment (and correspondingly the smallest increases in unemployment) during the crisis can be expected in countries where the EPL indexes and share of those employed on fixed-term employment contracts in total employment are moderate.
Keywords: 330; employment; unemployment; the global crisis; EU